2019
DOI: 10.1101/834788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurofibromin regulates metabolic rate via neuronal mechanisms in Drosophila

Abstract: 1Neurofibromatosis type 1 (NF1) is a genetic disorder predisposing patients to a range of 2 features, the most characteristic of which include areas of abnormal skin pigmentation and 3 benign tumors associated with peripheral nerves, termed neurofibromas. Less common, but 4 more serious symptoms also include malignant peripheral nerve sheath tumors, other 5 malignancies, and learning disabilities. The NF1 gene encodes neurofibromin, a large protein 6 that functions as a negative regulator of Ras signaling and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…This system uses indirect calorimetry to measure CO 2 release, while simultaneously measuring activity via counting infrared beam crosses (Fig 3A; Brown et al, 2022; Stahl et al, 2017). In agreement with previous findings, sleep was reduced in Nf1 P1 mutants in the SAMM system, and the total metabolic rate (VCO 2 ) was elevated during the day and the night compared to controls (Fig S5A,B; Botero et al, 2021). Similar effects were observed upon pan-neuronal knockdown of Nf1 (Fig S5C,D).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This system uses indirect calorimetry to measure CO 2 release, while simultaneously measuring activity via counting infrared beam crosses (Fig 3A; Brown et al, 2022; Stahl et al, 2017). In agreement with previous findings, sleep was reduced in Nf1 P1 mutants in the SAMM system, and the total metabolic rate (VCO 2 ) was elevated during the day and the night compared to controls (Fig S5A,B; Botero et al, 2021). Similar effects were observed upon pan-neuronal knockdown of Nf1 (Fig S5C,D).…”
Section: Resultssupporting
confidence: 93%
“…Studies in mammalian models have revealed a robust role for Nf1 in sleep and metabolic regulation, raising the possibility that they contribute to the complex systems in humans (Anastasaki et al, 2019; Tritz et al, 2021). In Nf1 -deficient Drosophila , metabolic rate is chronically elevated, sleep is shortened, and circadian rhythms are dysregulated in Nf1 mutants (Bai et al, 2018; Bai & Sehgal, 2015; Botero et al, 2021; King et al, 2016; Machado Almeida et al, 2021; Maurer et al, 2020; Williams et al, 2001), suggesting deep evolutionary conservation of Nf1 function. The findings that Nf1 plays a conserved role in regulating both sleep and metabolic rate raises the possibility that Nf1 is a critical integrator of these processes and that it may play a role in various forms of metabolic dysfunction that are associated with sleep disturbance (Arble et al, 2015; Depner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, loss of NF1 leads to excessive Ras and diminished cAMP/PKA signalling (Bergoug et al, 2020). Moreover, levels of phosphorylated MAPK have been shown to be augmented in the NF1 P1 mutant, indicative of excessive Ras activity (Botero et al, 2021;Williams et al, 2001). Therefore, we investigated which of these biochemical functions, if either, might explain the role of NF1 in regulating synaptic transmission and larval mechanoreception.…”
Section: Increased Ras Signalling Underlies Impaired Synaptic Transmi...mentioning
confidence: 99%
“…Altogether, these observations suggest that neurofibromin haploinsufficiency affects uptake, storage, and expenditure of energy [23,30,67]. In a recent study, Botero et al [68] showed that neurofibromin regulates metabolic homeostasis in Drosophila, increasing the metabolic rate, feeding, and energy homeostasis via actions on a central neuronal circuit.…”
Section: Table 1 Comparison Of Head Circumference and Anthropometric ...mentioning
confidence: 99%